The State of Interbank Competition in the Russian Banking Market - O. Yu. Donetskova (Управленческие науки)
In the conditions of economic turbulence, it is important to develop new approaches to banking business management. The purpose of the study is to identify trends in Bank management in the context of interbank competition. The stated goal of the paper requires solving specific problems that characterize the logic of the research: to clarify the theoretical aspects of Bank management in the context of interbank competition; to review the current state of banks and identify areas of their business management; to recommend measures aimed at the sustainable position of banks. There have been used General scientific methods of analyzing statistical data and analytical reviews of the Bank of Russia. The works of foreign and domestic economists on the issues of bank management and the state of interbank competition serve as a theoretical and methodological base. The author identified the trend of strong concentration of assets and liabilities of mainly state-owned banks located in the Central Federal district of the country; identified the problem of oligopoly and Sberbank’s dominance in all segments of the banking market. The totality of the obtained results allowed the author to conclude that interbank competition is becoming more intense. Based on systematic and integrated approaches, there have been suggested measures aimed at ensuring transparency of the banking business, equal position of participants in the market and their stability. This determines the scientific and practical significance of the research. The results of the study can be used by the mega-regulator and Bank managers to progress a business development strategy, as well as by economists for further research.